Ovary tumor by Sertoli-Leydig cells tumor - A case report and review of the literature - Caran, Eliana M. Monteiro (2022)
The authors report a case of a Sertoli-Leydig cell tumor (SLCT), stage Ia, in the right ovary of a 10-year-old girl. The initial clinical manifestations were pain and abdominal distention. A physical examination revealed a large abdominal tumor located in the central region of abdomen. She didn ’t show signs of virilization. Manifestations of precocious puberty were not noticed. Laparotomy was performed, a right salpingo- oophorectomy with incision biopsy of the left ovary was carried out. Histopathologically, it was a well differentiated tumor without heterologous elements. The patient has been free of disease for 34 months, now. We think this case is the first report in the Brazilian medical literature index of SLCT in a child younger than 10 years of age.